Nanorod-shaped K2Ti8O17 catalyst with IrO2 nanoparticles loaded on surface as well as preparation method and application of nanorod-shaped K2Ti8O17 catalyst
By loading IrO2 nanoparticles on the surface of the nanorod-shaped K2Ti8O17 support, the problems of poor stability and Ir waste in an acidic oxidation environment are solved, and the uniform distribution of IrO2 nanoparticles and good acidic OER catalytic performance are achieved.
Patent Information
- Application Number
- CN202411771412.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing anode OER catalyst has poor stability in an acidic oxidation environment, low Ir element reserves and high cost, and the Ir load distribution and large load size of the support type catalyst lead to Ir waste.
IrO2 nanoparticles were loaded on the upper surface of the nanorod-shaped K2Ti8O17 carrier by room temperature reduction and thermal oxidation, and IrO2 nanoparticles were loaded on the multi-defect surface of the K2Ti8O17 carrier after crushing.
The uniform distribution of IrO2 nanoparticles on the support, small particle size, no agglomeration, the catalyst morphology is regular, and it has good acidic OER catalytic performance, which reduces the use amount and cost of Ir.
Smart Images

Figure CN119800434A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a nanorod-shaped K2Ti8O 17 Catalyst and its preparation method and application. Background Art
[0002] Proton exchange membrane acidic water electrolysis hydrogen production technology is currently widely recognized as the most promising green hydrogen production technology, with advantages such as high-purity hydrogen production, compact structure, low operating cost, and fast load response, which is of great significance in solving environmental problems and energy shortages. However, the problem that currently hinders the promotion and application of this technology is its high cost investment, which urgently needs to be optimized, and the most intuitive of which is the anode OER (oxygen evolution reaction) catalyst.
[0003] OER is a 4-electron process with the characteristics of high reaction barrier and slow kinetics. At the same time, due to the evolution of oxygen, the anode catalyst actually works in a strong oxidizing and acidic environment, which places high demands on its stability. In the selection of anode catalyst materials, considering the poor stability of common elements under acidic oxidizing conditions, only Ir and its oxides can achieve relatively mature commercial applications. However, the reserves of Ir element are low and the cost is high, so modification optimization is urgently needed to reduce costs and increase efficiency. Among the current catalyst modification strategies, the introduction of a carrier is a very effective solution that can significantly reduce the loading of precious metals while ensuring the activity of the catalyst, and has become a research focus in recent years.
[0004] At present, researchers have developed and designed a series of unique supported catalysts, which have achieved the reduction of Ir loading and the improvement of catalytic activity, reflecting the great potential of supported catalysts, such as patents CN114990615A and CN115369422A. However, existing supported catalysts still face the problems of uneven distribution of defects on the support surface, unsatisfactory Ir loading distribution due to low density, and Ir waste caused by large loading size.
[0005] At the same time, in the Ir loading process, the currently widely used mixed salt oxidation method also has problems such as low loading density, excessively large loaded particle size, and even Ir agglomeration, which seriously hinders the realization of the carrier's advantages, such as patents CN116329561A and CN116377481A. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a nanorod-shaped K2Ti8O 17 Catalyst and its preparation method and application, nanorod-shaped K2Ti8O 17Nanorod-shaped K2Ti8O with IrO2 nanoparticles loaded on the surface was prepared by simple room temperature reduction and thermal oxidation method. 17 Catalyst, IrO2 nanoparticles in nanorod-shaped K2Ti8O 17 The loading uniformity on the carrier is high, the particle size is small, there is no agglomeration phenomenon, the catalyst morphology is regular, and it has good acidic OER catalytic performance; the preparation method is simple, the controllability is good, and the results are highly reproducible.
[0007] In order to solve the above technical problems, the present invention provides a nanorod-shaped K2Ti8O2 nanoparticle loaded with IrO2 nanoparticles on the surface. 17 The method for preparing the catalyst comprises the following steps:
[0008] S1, K2Ti8O 17 Nanowires were crushed to obtain nanorod-shaped K2Ti8O 17 ;
[0009] S2, the nanorod-shaped K2Ti8O 17 Mixing with IrCl3·3H2O and solvent to obtain a dispersed suspension;
[0010] S3, adding a reducing agent to the dispersed suspension, and obtaining nanorod-shaped K2Ti8O with Ir loaded on the surface after reaction. 17 Intermediate materials;
[0011] S4, placing the intermediate material in an aerobic environment at 250-550° C., and obtaining the nanorod-shaped K2Ti8O2 with IrO2 nanoparticles on the surface after reaction. 17 catalyst.
[0012] The present invention adopts a hydrothermal method to synthesize nanowire-shaped K2Ti8O with multiple surface defects. 17 , and crushed it to adjust the size to obtain nanorod-shaped K2Ti8O 17 The carrier is mixed with IrCl3·3H2O and a solvent to obtain a dispersed suspension. The solvent is heated to dissolve the IrCl3·3H2O. The reaction process does not require heating. Under the action of a reducing agent, Ir is loaded on the surface of the multi-defective nanorod-shaped carrier. After a thermal oxidation reaction, nanorod-shaped K2Ti8O with IrO2 nanoparticles loaded on the surface is obtained. 17 Catalyst. Nanorod-shaped K2Ti8O 17 The IrO2 nanoparticles loaded on the surface of the carrier are highly uniform and small in size, with a particle size as small as a few nanometers. There is no agglomeration phenomenon, the catalyst has a regular shape, and has good acidic OER catalytic performance. It can be widely used in the oxygen evolution reaction of acidic water electrolysis to produce hydrogen; the preparation method is simple, controllable, and the results are highly reproducible.
[0013] The K2Ti8O with multiple surface defects in the present invention 17 The microstructure of the carrier determines its excellent charge transfer ability, and the crushed K2Ti8O 17 The surface of the carrier has a higher density of defects and active sites, which can load IrO2 nanoparticles more evenly.
[0014] Furthermore, the solvent is deionized water, which can be partially mixed with K2Ti8O 17 Mixing, partially mixing with IrCl3·3H2O, or any other method of mixing the three to form a dispersed suspension.
[0015] Furthermore, the nanorod-shaped K2Ti8O 17 The diameter is 20-200nm, for example 20nm, 30nm, 50nm, 75nm, 100nm, 200nm, etc., including but not limited to this, and the length is less than 1μm, for example 50nm, 100nm, 200nm, 500nm, 600nm, 800nm, etc., including but not limited to this.
[0016] Furthermore, the particle size of the IrO2 nanoparticles is 1-100nm, for example, 1nm, 5nm, 10nm, 20nm, 50nm, 75nm, 100nm, etc., including but not limited to these. The size of the IrO2 nanoparticles is affected by the concentration of IrCl3·3H2O in the dispersed suspension. The size of the IrO2 nanoparticles can be regulated by regulating the concentration of IrCl3·3H2O in the dispersed suspension.
[0017] Furthermore, the K2Ti8O 17 The mass ratio of IrCl3·3H2O is (1-5):(1-5).
[0018] Furthermore, the reducing agent is one or more of ammonia water, sodium borohydride, and citric acid.
[0019] Furthermore, the amount of the reducing agent is greater than or equal to the amount of the IrCl3·3H2O.
[0020] Furthermore, the crushing treatment method is one or more of ultrasound, grinding and ball milling.
[0021] Further, in S3, the reaction time is 2-20h;
[0022] And / or, after the reaction, the step of washing the precipitate with deionized water and drying is further included, and the drying temperature is 50-80°C.
[0023] Furthermore, in S4, the reaction time is 0.5-5h.
[0024] The second aspect of the present invention provides a nanorod-shaped K2Ti8O2 with surface loaded IrO2 nanoparticles prepared by the preparation method of the first aspect. 17 catalyst.
[0025] The third aspect of the present invention provides a nanorod-shaped K2Ti8O2 having a surface loaded with IrO2 nanoparticles as described in the second aspect. 17 The catalyst is used as an oxygen evolution reaction catalyst in the production of hydrogen by acidic water electrolysis.
[0026] Beneficial effects of the present invention:
[0027] The present invention uses nanorod-shaped K2Ti8O 17 Nanorod-shaped K2Ti8O with IrO2 nanoparticles loaded on the surface was prepared by room temperature reduction and thermal oxidation. 17 Catalyst, IrO2 nanoparticles in nanorod-shaped K2Ti8O 17 The loading uniformity on the carrier is high, the particle size is small, there is no agglomeration phenomenon, and the catalyst morphology is regular.
[0028] The supported catalyst prepared by the method of the present invention has excellent acidic OER catalytic performance and can be widely used in fields such as acidic water electrolysis to produce hydrogen.
[0029] The preparation method of the invention is simple, low in cost, good in controllability, high in result repeatability, and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The nanorod-shaped K2Ti8O2 with surface-loaded IrO2 nanoparticles prepared in Example 1 of the present invention 17 Transmission electron microscope photo of the catalyst;
[0032] Figure 2 is a scanning electron microscope photograph of the IrO2-loaded TiO2 particle catalyst prepared in Comparative Example 1 of the present invention;
[0033] Figure 3 The surface-loaded IrO2 nanorod-shaped K2Ti8O 17 SEM images of the catalyst.
[0034] Figure 41 is the linear polarization curve of the catalyst prepared in the examples of the present invention and the comparative example. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] This embodiment provides a nanorod-shaped K2Ti8O 17 The method for preparing the catalyst comprises the following steps:
[0037] S1, K2Ti8O 17 Nanowires were crushed to obtain nanorod-shaped K2Ti8O 17 ;
[0038] Wherein, the solvent is deionized water, which can be partially mixed with K2Ti8O 17 mixing, partially mixing with IrCl3·3H2O, or any other method of mixing the three to form a dispersed suspension;
[0039] S2, the nanorod-shaped K2Ti8O 17 Mixing with IrCl3·3H2O and solvent to obtain a dispersed suspension;
[0040] Wherein, the K2Ti8O 17 The mass ratio of IrCl3·3H2O is (1-5): (1-5)
[0041] S3, adding a reducing agent to the dispersed suspension, and obtaining nanorod-shaped K2Ti8O with Ir loaded on the surface after reaction. 17 Intermediate materials;
[0042] The reaction time is 2-20 hours, and after the reaction, the steps of washing the precipitate with deionized water and drying are included, and the drying temperature is 50-80°C.
[0043] S4, placing the intermediate material in an aerobic environment at 250-550° C., reacting for 0.5-5 hours to obtain the nanorod-shaped K2Ti8O2 with IrO2 nanoparticles on the surface. 17 catalyst.
[0044] As a specific example, the nanorod-shaped K2Ti8O 17The diameter is 20-200nm, such as 20nm, 30nm, 50nm, 75nm, 100nm, 200nm, etc., including but not limited to this, and the length is less than 1μm, such as 50nm, 100nm, 200nm, 500nm, 600nm, 800nm, etc., including but not limited to this. The particle size of the IrO2 nanoparticles is 1-100nm, such as 1nm, 5nm, 10nm, 20nm, 50nm, 75nm, 100nm, etc., including but not limited to this. The size of the IrO2 nanoparticles is affected by the concentration of IrCl3·3H2O in the dispersed suspension. The size of the IrO2 nanoparticles can be regulated by regulating the concentration of IrCl3·3H2O in the dispersed suspension.
[0045] As a specific example, the reducing agent is one or more of ammonia water, sodium borohydride, and citric acid, and the amount of the reducing agent is greater than or equal to the amount of the IrCl 3 ·3H 2 O.
[0046] As a specific example, the crushing treatment method is one or more of ultrasound, grinding and ball milling.
[0047] This example uses a hydrothermal method to synthesize nanowire-shaped K2Ti8O with multiple surface defects. 17 , and crushed it to adjust the size to obtain nanorod-shaped K2Ti8O 17 The carrier is mixed with IrCl3·3H2O and a solvent to obtain a dispersed suspension. The solvent is heated to dissolve the IrCl3·3H2O. The reaction process does not require heating. Under the action of a reducing agent, Ir is loaded on the surface of the multi-defective nanorod-shaped carrier. After a thermal oxidation reaction, nanorod-shaped K2Ti8O with IrO2 nanoparticles loaded on the surface is obtained. 17 catalyst.
[0048] K2Ti8O with multiple surface defects 17 The microstructure of the carrier determines its excellent charge transfer ability, and the crushed K2Ti8O 17 The surface of the carrier has a higher density of defects and active sites, which can load IrO2 nanoparticles more evenly.
[0049] This example shows nanorod-shaped K2Ti8O 17 The IrO2 nanoparticles loaded on the surface of the carrier are highly uniform and small in size, with a particle size as small as a few nanometers. There is no agglomeration phenomenon, the catalyst has a regular shape, and has good acidic OER catalytic performance. It can be widely used in the oxygen evolution reaction of acidic water electrolysis to produce hydrogen; the preparation method is simple, controllable, and the results are highly reproducible.
[0050] Another embodiment provides a nanorod-shaped K2Ti8O2 with IrO2 nanoparticles on its surface prepared by the preparation method described in the above embodiment. 17 catalyst.
[0051] Another embodiment provides the nanorod-shaped K2Ti8O2 having IrO2 nanoparticles loaded on the surface as described in the above embodiment. 17 The catalyst is used as an oxygen evolution reaction catalyst in the production of hydrogen by acidic water electrolysis.
[0052] The following are specific embodiments.
[0053] Example 1
[0054] This embodiment relates to a nanorod-shaped K2Ti8O 17 The method for preparing the catalyst comprises the following steps:
[0055] 1) Add 0.03 g of K2Ti8O to a 50 mL beaker. 17 Nanowires and 25 mL of water were ultrasonically treated for 30 min and stirred to 17 The nanowires are crushed;
[0056] 2) Add 0.02 g of IrCl3·3H2O and 25 mL of 50°C water, stir evenly to obtain a dispersed suspension;
[0057] 3) The dispersed suspension was stirred and 0.06 g of sodium borohydride was added thereto, and the reaction was allowed to proceed overnight;
[0058] 4) washing the precipitate with deionized water and drying the precipitate in an oven at 60°C;
[0059] 5) The dried sample was heated to 350°C in a muffle furnace, kept warm for 2 hours, and then taken out after cooling to room temperature to obtain nanorod-shaped K2Ti8O with IrO2 nanoparticles loaded on the surface. 17 Supported catalyst.
[0060] The catalyst prepared in this example was analyzed by transmission electron microscopy. Figure 1 From a and b in Figure 1, we can see that the diameter of IrO2 nanoparticles is about 3.5nm, and the diameter of nanorods is about 55nm. 17 Evenly distributed on the carrier.
[0061] Comparative Example 1
[0062] This comparative example relates to a method for preparing a TiO2 particle catalyst loaded with IrO2, comprising the following steps:
[0063] 1) Add 0.03 g of TiO2 and 25 mL of water into a 50 mL beaker, ultrasonicate for 30 min and stir;
[0064] 2) Add 0.02 g of IrCl3·3H2O and 25 mL of 50°C water, stir evenly to obtain a dispersed suspension;
[0065] 3) The dispersed suspension was stirred and 0.06 g of sodium borohydride was added thereto, and the reaction was allowed to proceed overnight;
[0066] 4) washing the precipitate with deionized water and drying the precipitate in an oven at 60°C;
[0067] 5) The dried sample was heated to 350° C. in a muffle furnace, kept at this temperature for 2 hours, and then taken out after being cooled to room temperature to obtain an IrO2-loaded TiO2 particle catalyst.
[0068] The catalyst prepared in this comparative example was analyzed by scanning electron microscopy. Figure 2 From a and b in the figure, it can be seen that particulate TiO2 loaded with IrO2 is formed. In addition to the particles loaded on the surface, there are also many independent small-sized IrO2 clusters. The clusters are composed of particle agglomerations with a diameter of about 20nm, and the overall size of the clusters varies between 50-500nm.
[0069] Comparative Example 2
[0070] This comparative example relates to a nanorod-shaped K2Ti8O loaded with IrO2. 17 The preparation method of the catalyst comprises the following steps:
[0071] 1) 0.03 g of K2Ti8O 17 The nanowires and 0.02 g of IrCl3·3H2O were ground and mixed to obtain a reaction mixture;
[0072] 2) The reaction mixture was transferred to a porcelain boat, heated to 350°C in a muffle furnace, kept warm for 2 hours, and then taken out after cooling to room temperature to obtain nanorod-shaped K2Ti8O loaded with IrO2. 17 catalyst.
[0073] The catalyst prepared in this comparative example was analyzed by scanning electron microscopy. Figure 3 In a and b, it can be seen that the nanorod-shaped K2Ti8O 17 The carrier is loaded with IrO2 nanoparticles, and there are also many independent IrO2 clusters, among which K2Ti8O 17 The length of the carriers varies between 200-850 nm, and the size of the loaded IrO2 nanoparticles is approximately 15 nm in diameter.
[0074] In summary, the nanorod-shaped K2Ti8O prepared in the embodiment of the present invention 17 The IrO2 nanoparticles loaded on the carrier surface have high uniformity and small particles, with a particle size as small as 3 nanometers, no agglomeration, and a regular catalyst shape. This is due to the K2Ti8O 17 The microstructure of the carrier determines its excellent charge transfer ability, and the crushed K2Ti8O 17 The surface of the carrier has a higher density of defects and active sites, which can load IrO2 nanoparticles more evenly.
[0075] Application Examples
[0076] The catalysts of Example 1 and Comparative Examples 1-2 were tested for catalytic performance. The catalysts prepared in Example 1 and Comparative Examples were coated on the surface of the working electrode (glassy carbon electrode), the counter electrode was a platinum sheet, the reference electrode was a standard hydrogen electrode, and the electrolyte was a 0.5M sulfuric acid solution. The linear polarization curves of the three are shown in FIG. Figure 4 The catalysts prepared in Example 1 and Comparative Examples 1-2 were -2 The overpotentials under the current density are 254 mV, 590 mV, and 388 mV, respectively. It can be seen that the catalyst prepared in Example 1 of the present invention has better catalytic performance.
[0077] It can be seen that the catalyst prepared in the embodiment of the present invention has better acidic OER catalytic performance, because the nanorod-shaped K2Ti8O 17 The IrO2 nanoparticles loaded on the surface of the carrier have high uniformity and small particles, the particle size can be as small as 3 nanometers, there is no agglomeration phenomenon, and the catalyst has a regular shape, thus having better catalytic performance. The catalyst prepared in the embodiment of the present invention can be widely used in the oxygen evolution reaction of acidic water electrolysis to produce hydrogen.
[0078] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A nanorod-shaped K2Ti8O with surface-loaded IrO2 nanoparticles 17 The method for preparing a catalyst is characterized in that: The steps include: S1, K2Ti8O 17 Nanowires were crushed to obtain nanorod-shaped K2Ti8O 17 ; S2, the nanorod-shaped K2Ti8O 17 Mixing with IrCl3·3H2O and solvent to obtain a dispersed suspension; S3, adding a reducing agent to the dispersed suspension, and obtaining nanorod-shaped K2Ti8O with Ir loaded on the surface after reaction. 17 Intermediate materials; S4, placing the intermediate material in an aerobic environment at 250-550° C., and obtaining the nanorod-shaped K2Ti8O2 with IrO2 nanoparticles on the surface after reaction. 17 catalyst.
2. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: The nanorod-shaped K2Ti8O 17 The diameter is 20-200nm and the length is less than 1μm.
3. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: The K2Ti8O 17 The mass ratio of IrCl3·3H2O is (1-5):(1-5).
4. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: The reducing agent is one or more of ammonia water, sodium borohydride and citric acid.
5. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: The amount of the reducing agent is greater than or equal to the amount of the IrCl3·3H2O.
6. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: The crushing treatment method is one or more of ultrasound, grinding and ball milling.
7. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: In S3, the reaction time is 2-20h; And / or, after the reaction, the step of washing the precipitate with deionized water and drying is further included, and the drying temperature is 50-80°C.
8. The nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 1 17 The method for preparing a catalyst is characterized in that: In S4, the reaction time is 0.5-5h.
9. A nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles obtained by the preparation method according to any one of claims 1 to 8 17 catalyst.
10. A nanorod-shaped K2Ti8O2 having surface-loaded IrO2 nanoparticles as claimed in claim 9. 17 The catalyst is used as an oxygen evolution reaction catalyst in the production of hydrogen by acidic water electrolysis.
Citation Information
Patent Citations
Preparation method of noble metal powder catalyst for producing hydrogen by electrolyzing water
CN115198285A
TiZrO-IrO2-based oxygen evolution catalyst as well as preparation method and application thereof
CN118256952A
Synthesis method and application of acid-resistant conductive titanate
CN118480800A
Catalyst layer, membrane electrode assembly
US20230250543A1
High surface area, high porosity iridium-based catalyst and method of making
US20240218538A1